Analysis of Treponema pallidum Strains From China Using Improved Methods for Whole-Genome Sequencing From Primary Syphilis Chancres - Chen, Wentao; Šmajs, David; Hu, Yongfei; Ke, Wujian; Pospíšilová, Petra; Hawley, Kelly L; Caimano, Melissa J; Radolf, Justin D; Sena, Arlene; Tucker, Joseph D; Yang, Bin; Juliano, Jonathan J; et al. (The Journal of infectious diseases, 2021)
BACKGROUND: Whole-genome sequencing (WGS) of Treponema pallidum subspecies pallidum (TPA) has been constrained by the lack of in vitro cultivation methods for isolating spirochetes from patient samples. METHODS: We built upon recently developed enrichment methods to sequence TPA directly from primary syphilis chancre swabs collected in Guangzhou, China. RESULTS: By combining parallel, pooled whole-genome amplification with hybrid selection, we generated high-quality genomes from 4 of 8 chancre-swab samples and 2 of 2 rabbit-passaged isolates, all subjected to challenging storage conditions. CONCLUSIONS: This approach enabled the first WGS of Chinese samples without rabbit passage and provided insights into TPA genetic diversity in China.
Keywords: Syphilis; Animals; whole-genome sequencing; Rabbits; syphilis; chancre; králíci; lidé; tvrdý vřed; zvířata; Treponema pallidum; syfilis; sekvenování celého genomu; Chancre; Whole Genome Sequencing; China; Čína; Humans